Gambaran makroskopik dan mikroskopik kandung kemih pada hewan coba postmortem - Pontoh, Larisa M.; Kalangi, Sonny J.R.; Kaseke, Martha M. (Universitas Sam Ratulangi, 2017)
Abstract: The aim of this study was to obtain the microscopic and microscopic postmortem changes of urinary bladder in domestic pigs. This was a descriptive observational study. The observations were performed at several time intervals, as follows: 1, 2, 3, 4, 5, 6, 9, 12, 15, 18, 21, 24, 30, 36, 42, and 48 hours postmortem. The macroscopic observation of urinary bladder showed that the organ color became darker at 2-3 hours postmortem, the consistency became soft at 24 hours postmortem, and the organ became flattened and longer at 24-30 hours postmortem. The microscopic changes were epithelial desquamation at 1 hour postmortem which was continued leaving a flat thin basal layer at 24 hours postmortem. Congestion was observed at 1 hour postmortem. Hydropic degeneration of the muscle layer began at 3hours postmortem, and the layer became unidentified at 42 hours postmortem. Epithelial changes were hydropic degeneration, picnotic, and anuclear at 4 hours and were identified until 21 hours postmortem. Debris of necrotic epithelial cells was observed until 36-48 hours postmortem. Conclusion: The earliest macroscopic change started at 3 hours postmortem was the change in color. The earliest microscopic changes started at 1 hour postmortem were epithelial desquamation and congestion.Keywords: macroscopic, microscopic, urinary bladder, postmortemÂ Abstrak: Tujuan penelitian ini untuk mengetahui gambaran perubahan makroskopik dan mikroskopik kandung kemih hewan coba babi postmortem. Jenis penelitian ialah deskriptif observasional. Perubahan diamati pada beberapa interval waktu postmortem: 1 jam, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 9 jam, 12 jam, 15 jam, 18 jam, 21 jam, 24 jam, 30 jam, 36 jam, 42 jam, dan 48 jam. Hasil pengamatan makroskopik mendapatkan perubahan warna kandug kemih menjadi lebih gelap dari 2 jam ke 3 jam postmortem, konsistensi berubah dari kenyal menjadi lunak sampai 24 jam postmortem, organ mengempis dan memanjang pada 24 jam sampai 30 jam postmortem. Perubahan mikroskopik berupa deskuamasi sejak 1 jam postmortem dan pada 24 jam postmortem tersisa epitel basal tipis dan rata. Kongesti terlihat sejak 1 jam postmortem. Degenerasi hidrofik pada lapisan otot sejak 3 jam postmortem sampai lapisan tersebut tidak jelas teramati 42 jam postmortem. Perubahan epitel berupa degenerasi hidrofik, inti piknotik, dan anukleus dimulai pada 4 jam postmortem dan terus berlanjut sampai 24 jam postmortem. Debris sel nekrosis terlihat pada 36 sampai 48 jam postmortem. Simpulan: Perubahan makroskopik mulai tampak pada 3 jam postmortem berupa perubahan warna. Perubahan mikroskopik mulai tampak pada 1 jam postmortem berupa deskuamasi epitel dan kongesti.Kata kunci: makroskopik, mikroskopik, kandung kemih, postmortem